Adaptation and validation of Overall Anxiety Severity and Impairment Scale (OASIS) in Bangla - Khan, Muntasir; Alam, Mohammad Tariqul; Parveen, Shahana; Sarkar, Ahsan Aziz (Bangladesh Journal of Psychiatry, 2024)
Anxiety disorders cast a significant shadow over individuals’ lives, affecting their physical, psychological, and social well-being. Several types of anxiety disorders are prevalent in Bangladesh. Using a disorder-specific scale for screening each anxiety disorder would be unwise in a busy healthcare setting. Recognizing the need for an effective screening and assessment tool for anxiety in the Bengali-speaking population, a cross-sectional validation study spanning from October 2018 to February 2023 successfully adapted and validated the overall anxiety severity and impairment scale (OASIS) for Bangla-speaking adults. OASIS is one of the shortest available anxiety screening tools and can assess multiple anxiety disorders within a short time. This ground-breaking study, conducted at the National Institute of Mental Health (NIMH) with approval from the Institutional Review Board (IRB), followed a meticulous adaptation process that included forward and backward translations, synthesis, and pilot testing. Clinically diagnosed 150 adults with anxiety disorder from the outpatient department who were administered an adapted version of OASIS, the Generalized Anxiety Disorder Scale 7 (GAD 7), and the WHO 5 wellbeing index (WHO-5) to assess the reliability and validity of OASIS Bangla version and data were analyzed using statistical package for social sciences (SPSS) 23 and classical and Bayesian instrument development (CBID) software. A significant strong positive correlation (r=0.861) was found between OASIS and GAD-7 which suggested strong convergent validity. Likewise, a strong negative correlation (r=-0.837) between OASIS and WHO-5 suggested strong divergent validity. Internal consistency measured by Cronbach’s alpha found was 0.834 and split-half reliability measured by Spearman Brown Coefficient found was 0.836. Confirmatory factor analysis of the proposed one-factor model had a chi-square/df value of less than 3; Root mean square error of approximation (RMSEA) value of 0.073; comparative fit Index (CFI) value of 0.997 and Tucker Lewis index (TLI) value of 0.994. An exploratory factor analysis by principal component analysis method with varimax rotation identified one factor with eigenvalues more than 1.0 and it explained 60.8% of the variance. All five items had factor loads of more than 0.60 and the final analysis yielded a single component. When the results were considered as a whole, the OASIS Bangla was found a valid and reliable tool to assess anxiety severity along with impairment for Bangladeshi people. Bang J Psychiatry 2023;37(2): 32-37